2016
DOI: 10.1016/j.jaac.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parent Training on Adaptive Behavior in Children With Autism Spectrum Disorder and Disruptive Behavior: Results of a Randomized Trial

Abstract: Objective: This study examined the impact of Parent Training on adaptive behavior in children with autism spectrum disorder (ASD) and disruptive behavior. Methods:This was a 24-week, six-site, randomized trial of parent training versus parent education in 180 children with ASD (age 3 to 7 years; 158 boys, 22 girls) and moderate or greater behavioral problems. Parent training included specific strategies to manage disruptive behavior over 11 to 13 sessions, 2 telephone boosters, and 2 home visits. Parent educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 17 publications
1
64
0
2
Order By: Relevance
“…Research has suggested that parents’ knowledge is important for the child’s improvement in daily life 41. However, it should not have an impact on equal care and support from authorities to the families.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that parents’ knowledge is important for the child’s improvement in daily life 41. However, it should not have an impact on equal care and support from authorities to the families.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Autism Speaks sponsored working group panel recommended the Vineland‐II as suitable (having adequate reliability, validity, and responsiveness) to quantify social communication deficits in clinical trials of ASD [Anagnostou et al, ; see also McConachie et al, ]. The Vineland‐II is also increasingly used in randomized trials targeting core ASD symptoms and/or adaptive behavior more broadly [e.g., Chugani et al, ; Dawson et al, ; Hardan et al, ; Scahill et al, ; Umbricht et al, ; Veenstra‐VanderWeele et al, ; Ventola et al, ], in part due to the relative lack of other reliable measures of change in these behaviors [Anagnostou et al, ]. This increasing use may also reflect the relatively broader scope of adaptive behaviors assessed by Vineland‐II, relative to the more circumscribed set of core ASD symptoms (McDougall et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…The VABS [57] is a widely-used parent interview measuring adaptive behaviour, recommended as a test-retest measure in autism treatment studies [58] and normed for all ages [59]. Items are categorised into four primary domains: communication, daily living skills, socialisation, and motor skills, with maladaptive behaviour (internalising and externalising) also examined.…”
Section: Parent Reports Vineland Adaptive Behavior Scales II (Vabs-2)mentioning
confidence: 99%